Peningkatan Kapasitas Kader Posyandu melalui Edukasi Gizi Seimbang dan Implementasi Buku RASA (Resep Anak Sehat dan Aktif) - Arizal, Andika; Maharani, Hanindyah Puteri; Apriyani, Nuri; Maulida, Siti; Santanu, Ayu Mutiara (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Nutritional problems in toddlers, including the high prevalence of stunting, indicate the need to strengthen the capacity of Posyandu cadres who play a leading role in nutrition education for the community. This community service activity aims to improve the knowledge and skills of Posyandu cadres in applying the principles of balanced nutrition through counseling and implementation of the RASA (Healthy and Active Children's Recipes) Book as a medium for continuous education. The methods used were Community Education through lectures, question and answer sessions, and Science and Technology Dissemination, and were evaluated using a one group pretest-posttest design. The results showed an increase in knowledge scores, from 86.8% to 91.9% after the counseling activity. The cadres responded positively to the RASA Book, which was considered practical and easy to apply in posyandu activities. This confirms that educational activities using educational media are effective in increasing the capacity of cadres, thereby strengthening stunting prevention efforts at the community level.